Cadeias produtivas e complexos industriais da economia fluminense - Elydia Mariana Goncalves da Silva (2007)
Through the identification of the key sectors and industrial complexes in Rio de Janeiro state, this work proposed the discussion and understanding of its productive structure. Some tests were applied on the Input-Output Model which included an inter-regional matrix for Rio de Janeiro and Minas Gerais states, Northeast and the rest of Brazil for 1990, and a national matrix for 2003. It was found some fragility on the states productive structure arised from its weak sectorial and inter-sectorial integration. The state seems to be very dependent of commercial relationships with its own region and with Sao Paulo. Moreover, it was found that, although Rio is an important producer of inputs produced by oil derivatives and steel industry sectors for the country, its potential is not fully used for its own industrial development.